ANALISIS PERPUTARAN MODAL KERJA PADA PT. AKASHA WIRA INTERNASIONAL TBK TAHUN 2017-2021 - Waoma, Sri Fidelty (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
The purpose of this study is to determine the working capital turnover and also explain the parts of the working capital turnover. This research method is aqualitative research with a descriptive nature. The data used is secondary data. The data collection technique is to collect data in the form of financial reports at PT. Akasha Wira Internasional Tbk. Year 2017-2021. The data analysis method used in this study is to use financial ratios including, inventory turnover, cash turnover, accounts receivable turnover and working capital. The results of this study indicate that the turnover of working capital at PT. Akasha Wira Internasional Tbk. In 2017-2021, based on the working capital turnover ratio, it is very slow, resulting in ineffective working capital turnover and a low working capital turnover rate. So it can be concluded that the company is still less effective in using its working capital so that it can affect the maximum profit. The author suggests that to increase optimal profits, companies must be careful and need to be careful in using their working capital so that companies can obtain maximum profits.